Phosphophosphidites Derived from BINOL. Issue 11 (28th February 2019) - Gorman, Adam D.; Cross, Jessica A.; Doyle, Rachel A.; Leonard, Tom R.; Pringle, Paul G.; Sparkes, Hazel A.
Abstract : Phosphophosphidites of the type R2 P–P(binol) [where binol = the dianion of (S)‐1, 1′‐bi‐2‐naphthol] are the phosphorus analogues of the ubiquitous phosphoramidites, R2 N–P(binol) and are readily accessed by the chlorosilane elimination reaction between R2 P–SiMe3 and Cl–P(binol). The crystal structure of i Pr2 P–P(binol) (1 ) has been determined and shows a P–P bond length in the normal range. The solution reactions of 1 have been investigated, principally by 31 P NMR spectroscopy which has revealed that: (a) in contrast to the phosphoramidites, 1 is extremely moisture sensitive; (b) the P–P bond in 1 is cleaved upon reaction with H2 O, MeOH or mesitol; (c) the P–O bonds in 1 are cleaved upon reaction with pyrrolidine; (d) the integrity of 1 is retained upon coordination to BH3 or Mo 0 . The crystal structure of cis ‐[Mo(CO)4 (1 )2 ] shows that 1 is bound to the Mo at the P(binol) site and the νCO of 2032 cm ‐1 indicates that 1 has similar ligand properties to a phosphonite. Abstract : The high reactivity of phosphophosphidite 1 contrasts with the inertness of its N‐analogue, phosphoramidite A . The P–P bond in 1 is readily cleaved by water or methanol but remains intact in the Lewis adducts of 1 with BH3 and in the complex [Mo(CO)4 (1 )2 ].